TFAP2C-Mediated lncRNA PCAT1 Inhibits Ferroptosis in Docetaxel-Resistant Prostate Cancer Through c-Myc/miR-25-3p/SLC7A11 Signaling - Jiang, Xingkang; Guo, Shanqi; Xu, Mengyao; Ma, Baojie; Liu, Ranlu; Xu, Yong; Zhang, Yangyi (Frontiers in Oncology, 2022)
Recent evidence has shown that the induction of ferroptosis is a new therapeutic strategy for advanced prostate cancer (PCa) when used as a monotherapy or in combination with second-generation antiandrogens. However, whether ferroptosis inducers are effective against docetaxel-resistant PCa remains unclear. In addition, the biological role and intrinsic regulatory mechanisms of long noncoding RNAs (lncRNAs) in ferroptosis and chemoresistance are not well understood. In this study, we established two acquired docetaxel-resistant PCa cell lines and found that docetaxel-resistant PCa cells developed tolerance toward ferroptosis. In addition, dysregulated lncRNAs in drug-resistant and -sensitive PCa cells were identified by RNA sequencing, and we identified that prostate cancer-associated transcript 1 (PCAT1) was highly expressed in the docetaxel-resistant PCa cell lines and clinical samples. Overexpression of PCAT1 inhibited ferroptosis and increased docetaxel resistance, which could be attenuated by PCAT1 knockdown. Furthermore, we revealed that PCAT1 inhibited ferroptosis by activating solute carrier family 7-member 11 (SLC7A11) expression via reducing iron accumulation and subsequent oxidative damage. Mechanistically, we demonstrated that PCAT1 interacted with c-Myc and increased its protein stability using nucleotides 1093-1367 of PCAT1 and 151-202 amino acids of c-Myc protein, thereby transcriptionally promoting SLC7A11 expression. In addition, PCAT1 facilitated SLC7A11 expression by competing for microRNA-25-3p. Finally, transcription factor AP-2 gamma (TFAP2C) activated PCAT1 expression at the transcriptional level to reduce ferroptosis susceptibility and enhance chemoresistance. Collectively, our findings demonstrated that TFAP2C-induced PCAT1 promotes chemoresistance by blocking ferroptotic cell death through c-Myc/miR-25-3p/SLC7A11 signaling.